Inclusive growth in India - "Dev, S.Mahendra" (New Delhi, 2008)
This book details the author's research in the last decade in understanding the need for economic reforms with 'human face' or equitable development. Indian experience with reforms in the last sixteen years reveals that there have been achievements on economic growth but inequalities have increased and exclusion continued. This book examines the performance, issues and challenges in most important and inter-related elements of inclusive growth: agriculture, poverty, food security and employment, social sector and, regional disparities. In order to achieve inclusive growth, the study argues for macro pro-poor and people centric policies. Since challenges for achieving inclusive growth are much more than raising economic growth, the volume also argues that public policy should give priority to the 'inclusive' sectors rather than concentrating on policies to improve lop sided growth benefiting few sections of the population. It also suggests that growth and equity objectives should be pursued simultaneously rather than growth in the first phase and equity in the next round. The book also emphasis on the importance of women's economic and social empowerment and socially disadvantaged sections like SCs and STs for realizing inclusive growth.
Keywords: Economic growth - India